Grammatical Features of African American Vernacular English In King of Killbranch Album - Rio Raka Fatra; Anit Pranita Devi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aimed to identify and analyze the grammatical features of African American Vernacular English (AAVE) used in King Of Killbranch album by BIG30. This research also aimed to identify the most dominant grammatical feature of African American Vernacular English (AAVE) used in King Of Killbranch album. A case study method was applied to this research. The grammatical features of AAVE were analyzed based on the theories proposed by Wolfram (2004). The data analysis procedures included reading the song lyrics, sorting and identifying song lyrics that contain AAVE grammatical features, and examining the data using Wolfram's theory. The results showed that 10 grammatical features were found such as copula absence, invariant